Transnational counselling networks of Polish emigrants - Aneta Słowik (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2017)
In the first part of the article the author presents her theoretical-methodological framework of the conducted research process. It is constituted of three elements: the conception of transnationality and the methodological basis for research of transnational networks, counsellogical reflection for identifying the subjects (counsellors and counsellees), counselling practices, acts and processes in the field of emigration as well as the method for analysis of drawings of networks by polish emigrants. In the second part of the article by employing the theoretical-methodological framework and on the basis of the collected evidential material (biographical interviews and drawings of the networks made by Polish emigrants), the author offers a typology of transnational counselling networks created byPolish people. In the concluding part some conclusions will be made. The different types of counselling subjects, processes, practices, and acts have influence on the structure, form and construction of the networks. The networks are hard to be generalized, they are very individual, transient, temporary, and they dissolve fast. The process of identification of transnational counselling networks should be treated as long-lasting and extended in time.